International legal framework for the regulation of judicial immunity - S. O. Demchenko (Law and Safety)
The article analyses the phenomenon of judicial indemnity through the prism of international legal regulation developed in Western Europe in recent decades. Based on the analysis of Ukrainian and European law, it has been concluded that the doctrine of limited judicial indemnity is currently dominant, which balances public interests and serves the freedom of expression and strengthening of the principles of independence in the structure of the legal status of a judge. It is demonstrated that the international legal regulation of judicial indemnity contributes to the institutional strengthening of the judiciary, enhancement of its authority in society, and awareness of the high mission of judges in establishing the rule of law, preventing and counteracting any manifestations of aggression against the judiciary which not only threaten its independence but also often deprive judges of the opportunity to legally express their opinions in public. Judicial indemnity is considered in the context of the concept of subjective human rights as a derivative of the fundamental right to freedom of expression. This indemnity belongs to professional judges in accordance with the concept of good faith. It is established that a judge's freedom of expression is possible both in his/her judicial and extrajudicial activities, which should be clearly reflected in the amendments to the Law of Ukraine “On the Judiciary and the Status of Judges”. The state guarantees judges protection from prosecution for their statements both in and out of court. In the Ukrainian context, the content and system of such guarantees require both regulatory and institutional strengthening. The scope of judicial indemnity protection varies depending on the legislation, rules of judicial ethics, specifics of the judicial system, authority of the judiciary, case law and legal traditions. Moreover, there are some peculiarities of the ‘cooling effect’ concept in the field of judicial indemnity. Finally, the author concludes that the key elements of the European Court of Human Rights case law relating to the essence of judicial indemnity and its limits should be adapted and integrated into the Ukrainian judicial system, given their importance for the development of the relevant doctrine.